URGENSI LOYALITAS KONSUMEN: ANTARA CORPORATE IMAGE ATAU CUSTOMER TRUST - Lusiani Lusiani; Iman Sidik Nusannas (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2019)
As an economic entity a bank has an important role in the country’s growth and development. The bank itself depend on their customers, a loyal and old customer . The loyal customers is an asset, so that this research is to find out the relationship berween customer trust and corporate image bya asking 100 customers. The sample was picked by using Simple Random Sampling method of Probability Sampling research technique. This study uses Product Moment analysis with the help of IBM SPSS Statistics 24 software for analyzing the primary data. The results of this study show that : 1) Corporate Image has positive and significant effects to Customer Loyality, 2) Customer Trust has positive and significant effect to Customer Loyality, 3) Corporate Image and Customer Trust simultaneously have positively effects to Customers Loyality. It is suggested to further expands the scope of this research to other institutions or business. Customer loyality is not only gained by Corporate Image and Customer Trust, but also the bank has to maintain good service for the existing customers. So the customers will be satisfied and loyal.